Untargeted plasma metabolite detection in sudden sensorineural hearing loss: identifying key metabolic signatures - Ma, Rongyue; Zhang, Huangruici; Wang, Weijie; Yu, Changping; Xiong, Guohang; Li, Qing; Wang, Yan; Zhou, Li; Zhang, Yu; Li, Min; Guo, Min (Frontiers in Molecular Biosciences, 2025)
BackgroundSudden sensorineural hearing loss (SSNHL) is a common otological disorder with complex etiologies and unclear pathophysiology. This study aimed to detect and analyze plasma metabolites in SSNHL, identify potential biomarkers, and uncover underlying metabolic mechanisms.MethodsA cohort of 64 SSNHL, classified into four subtypes (low-frequency, high-frequency, flat and total deafness type), and 53 normal controls (NC) were recruited. Plasma samples were collected and analyzed by high-performance liquid chromatography-mass spectrometry (LC-MS). Metabolite profiling was performed, followed by multivariate statistical analyses, including orthogonal projections to latent structures-discriminant analysis (OPLS-DA) and partial least-squares discriminant analysis (PLS-DA) to find differentially expressed metabolites between the groups.ResultsThe results showed significant differences in the plasma metabolome when comparing each of the four SSNHL types with NC. A total of 130 differentially expressed metabolites were identified, with sphingosine, anthranilic acid, and 6-hydroxyflavanone (6-HF) being prominent examples. Were prominent. Pathway enrichment analysis indicated that these metabolites were mainly involved in central carbon metabolism, protein digestion and absorption, aminoacyl-tRNA biosynthesis, mineral absorption, etc.ConclusionThese findings imply that plasma metabolite profiling holds promise as a non-invasive approach for screening biomarkers in SSNHL. The identified differential metabolites and associated metabolic pathways may offer novel perspectives on the pathophysiology of SSNHL, presenting potential targets for future therapeutic interventions.